Analisis Efektivitas Penerapan Sistem Informasi Akuntansi (SIA) Dalam Pengambilan Keputusan Strategis Pada UMKM Toko Besi Bima Raya Grup: (Pendekatan Model DeLone Dan McLean) - Beny Rachmanto; Dwiyani Sudaryanti; Nurhidayah Nurhidayah (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
The growth of Micro, Small, and Medium Enterprises (MSMEs) increasingly requires the utilisation of information technology capable of providing accurate and relevant data to support strategic decision-making. In this context, the implementation of an Accounting Information System (AIS) must be evaluated to ascertain its contribution to managerial performance. This study aims to examine the effectiveness of AIS implementation in supporting strategic decisions at the MSME Toko Besi Bima Raya Group by employing the DeLone and McLean Information Systems Success Model as an analytical framework. A qualitative approach with a case study design was adopted. Data were collected through in-depth interviews with the owner, store managers, cashiers, and operational staff, complemented by direct observation and examination of financial records. The data were analysed thematically based on six construct of the model: system quality, information quality, service quality, use, user satisfaction, and net benefits. The findings indicate that the system effectively supports daily operations through its ease of use and alignment with business requirements. The information generated is regarded as accurate, timely, and comprehensive in facilitating inventory management, cash flow monitoring, and sales evaluation. However, the service dimension requires further improvement, particularly regarding technical assistance and advanced feature development. The high frequency of system utilisation contributes to user satisfaction and results in improved stock control efficiency and enhanced quality of strategic decisions. It is concluded that AIS effectiveness depends on the integration of system quality, information quality, service support, and user experience, thereby necessitating continuous evaluation to sustain MSME performance.